The Effect of substrate Nature on the properties of Tin Sulfide Nanostructured films Prepared by chemical bath deposition - Al Hilli, Baha'a; Abood, Zahra'a A.; Mehdi, Muhammed Saleh (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
The substrate's nature plays an important role in the characteristics of semiconductor films because of the thermal and lattice mismatching between the film and the substrate. In this study, tin sulfide (SnS) nanostructured thin films were grown on different substrates (polyester, glass, and silicon) using a simple and low-cost chemical bath deposition technique. The structural, morphological, and optical properties of the grown thin films were investigated using X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM), and ultraviolet-visible-near infrared (UV-Vis-NIR) spectroscopy. The XRD and FESEM results of the prepared films revealed that each film is polycrystalline and exhibits both orthorhombic and cubic structure types. In addition, the deposited films on polyester and glass showed good absorption in the UV-Vis-NIR range.